Front Cover: Single‐Chain Magnet Based on Cobalt(II) Thiocyanate as XXZ Spin Chain (Chem. Eur. J. 13/2020). Issue 13 (4th February 2020) - Rams, Michał; Jochim, Aleksej; Böhme, Michael; Lohmiller, Thomas; Ceglarska, Magdalena; Rams, Marek M.; Schnegg, Alexander; Plass, Winfried; Näther, Christian
Abstract : The magnetic properties of single‐chain magnets investigated by sophisticated THz EPR spectroscopy are reported in this work. The cover artwork depicts an artistic view of Co II spins in a 1D coordination polymer that are flipped by impulses of synchrotron radiation during an EPR experiment. More information can be found in the Full Paper by M. Rams, C. Näther, et al. on page 2837 .